bbolker / math3mb

Mathematical Modelling at McMaster University
GNU General Public License v2.0
1 stars 1 forks source link

Condition for stability #6

Open xiaokev opened 6 years ago

xiaokev commented 6 years ago

Hello Dr. Bolker, I was looking over the notes from the start of class and I'm having trouble seeing the general condition for UDD stability |f'(N)|<1. In class you explained it using Taylor's theorem so f(N+e) = f(N)+ ef'(N) +... but since f'(N) = R in LUDD you would get f(N+e) = f(N)+ eR +... = N+eR. Wouldn't this mean if you move away from the equilibrium by e the population would be N+eR? How would |R|<1 cause the taylor expansion to be equal to N* on the right?

I was thinking that since f(N+e) is the population at say time t then N(t+1) = f(N(t)) = f(N+e) then the next time step would give N(t+2) =f(N(t+1)) = R(f(N+e)) = RN + eR^2 = N* (when you move further from time t) I'm not sure if this logic works as having population on both axis trips me up sometimes.

bbolker commented 6 years ago

First, you should be careful with notation. |f'(N*)|<1 means |f'(N)| (as a general expression in terms of N) evaluated at N is <1.

In the homogeneous LUDD case, N*=0. Then it's easy to see that

f(N*+e) = f(N*)+ef'(N*) + ...
f(e)       = 0 + eR + ...
            ~ eR

More generally (and including the non-homogeneous or affine LUDD case): start with f(N+e) = f(N) + ef'(N) + ... Then change variables so we are considering the distance from the equilibrium, i.e. N^ = N-N. Subtracting N* from both sides of the equation:

f(N*+e)-N* = f(N*) -N* + ef'(N*) + ...

The left-hand side is the change in N^. The right-hand side simplifies/approximates to ef'(N) (the first two terms cancel and the later terms are dropped), leaving us with (change in N^ = `N^ f'(N)`) when N^ is small.

Does that help?

xiaokev commented 6 years ago

so is N^ another recursive relation that resembles our N(t+1)=RN(t)?